2010
DOI: 10.1007/s12630-010-9387-0
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane does not alter norepinephrine-induced intracellular Ca2+ changes in the diabetic rat aorta

Abstract: Purpose The effect of volatile anesthetics on the mechanism(s) of vascular contraction in diabetes mellitus (DM) has not been fully understood. The current study was designed to determine the effects of sevoflurane on the norepinephrine (NE)-induced changes in contractile state and intracellular Ca 2? concentrations ([Ca 2? ] i ) in the spontaneously developing type 2 DM rat. Methods The effects of sevoflurane on NE (10 -6 M)-induced vasoconstriction and increase in [Ca 2? ] i in the aortas from Otsuka Long-Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The KCl/PI3K-C2α/Rho kinase/MLCP/MLC pathway may mediate the intracellular mechanism of VSM contraction induced by volatile anesthetics [21] . Fujii et al showed that SEVO did not alter the changes in Ca 2+ in aortic cells of diabetic rats induced by NE [23] , and SEVO at clinical concentrations could signi cantly inhibit the response of nondiabetic rats to NE but had no such effect on diabetic rats. Recent studies have shown that arterial reactivity to acetylcholine (ACh) and Ang II in diabetic mice is signi cantly changed, which is related to an increase in Rho kinase activity [27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KCl/PI3K-C2α/Rho kinase/MLCP/MLC pathway may mediate the intracellular mechanism of VSM contraction induced by volatile anesthetics [21] . Fujii et al showed that SEVO did not alter the changes in Ca 2+ in aortic cells of diabetic rats induced by NE [23] , and SEVO at clinical concentrations could signi cantly inhibit the response of nondiabetic rats to NE but had no such effect on diabetic rats. Recent studies have shown that arterial reactivity to acetylcholine (ACh) and Ang II in diabetic mice is signi cantly changed, which is related to an increase in Rho kinase activity [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SEVO at clinical concentrations can signi cantly inhibit the response of nondiabetic rats to norepinephrine (NE), but it has no effect on diabetic rats [23] . Clinical studies have also demonstrated that the foot skin temperature of nondiabetic patients is higher than that of diabetic patients induced by ISO or SEVO anesthesia, suggesting that thermoregulation controlled by the sympathetic nervous system is impaired in diabetic patients [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Fujii et al showed that SEVO did not alter the changes in Ca 2+ in aortic cells of diabetic rats induced by NE [ 25 ], and SEVO at clinical concentrations could significantly inhibit the response of nondiabetic rats to NE but had no such effect on diabetic rats. Recent studies have shown that arterial reactivity to acetylcholine (ACh) and Ang II in diabetic mice is significantly changed, which is related to an increase in Rho kinase activity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SEVO at clinical concentrations can significantly inhibit the response of nondiabetic rats to norepinephrine (NE), but it has no effect on diabetic rats [ 25 ]. Clinical studies have also demonstrated that the foot skin temperature of nondiabetic patients is higher than that of diabetic patients induced by ISO or SEVO anesthesia, suggesting that thermoregulation controlled by the sympathetic nervous system is impaired in diabetic patients [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports also showed that SEVO decreased myofilament Ca 2+ sensitivity by regulating Rho kinase and PKC activity [ 1 , 17 , 18 ]. We recently showed that SEVO does not alter norepinephrine-induced intracellular Ca 2+ changes in the diabetic rat aorta [ 28 ]. These data further demonstrate that myofilament Ca 2+ sensitization, not Ca 2+ -dependent mechanisms, is involved in modulating vascular tension by SEV.…”
Section: Discussionmentioning
confidence: 99%